An expected shot outcome model for points in elite Gaelic football - McDaid, K.; McGuigan, K.; McDonnell, J.; Collins, K. (International Journal of Performance Analysis in Sport, 2025)
This study develops a logistic regression model to predict the likelihood of scoring a point in Gaelic football based on shot characteristics. A total of 3537 shots from 67 elite inter-county games in 2019 are analysed. The findings indicate that shot distance, pressure, type (open play/dead ball), side and team level are significant predictors in the model with shots from open play significantly less likely to result in scores than shots from dead ball situations. Pressure is found to be a key to the model with the model indicating that taking a shot under high pressure as compared to low pressure is similar to taking the shot from approximately 9 m further away. Also, interaction effects between shot type and distance, type and angle, and side and method are found to be significant with the outcome that shots from the left side of the field with the right foot are most likely to be successful. The variation in the difference between expected and actual scores for games is found to be similar across team levels.